Management and prevention of burnout in professional nurses - Tongprapai, Kessara; Sethabouppha, Hunsa (Thai Journal of Nursing, 2025)
To date there are not enough nurses in the system to provide health services. In addition, more nurses are resigning because they cannot manage their own problems or emotions, have conflicts with colleagues, client, or client’s relatives, organization management that is not conducive to the nursing profession, and work conditions that must deal with serious and complex health problems. Compensation is not worth the work, affecting nurses, causing stress to accumulate for a long time, and being unable to manage stress effectively, leading to burnout. Therefore, managing and preventing burnout in nurses, both at the individual and organization levels, is important. At the individual level, nurses themselves should consider seeking social support, managing their emotions, learning new skills, and maintaining healthy behaviors. In term of organization level, there should be policies to address burnout, promote employee engagement, and create a positive work environment.